Ideal Formulation of Police Efforts in Combating the Distribution of Crystal Meth Among Students (Case Study at Cirebon City Police Resort) - Lestari, Sri Ayu; Winjaya Laksana, Andri (UNISSULA Semarang, 2025)
Abstract. Illegal drug trafficking and abuse that has targeted the young and old generations has reached various remote areas and drug abuse is often referred to as narcotics is almost evenly distributed in all levels of society. Legislation governing drugs is needed to stop the illegal drug trafficking, which always leads to drug abuse. The purpose of this study is to determine and analyze police efforts in overcoming the circulation of crystal methamphetamine among students today. To determine and analyze the obstacles faced by the police in overcoming the circulation of crystal methamphetamine among students today. The sources and types of data in this study are primary data obtained through interviews and secondary data obtained from literature studies. The data is analyzed qualitatively using crime prevention theory, legal system theory and progressive legal theory. Based on the results of the study, the police's efforts in overcoming the crime of methamphetamine abuse among students are currently being carried out through preventive efforts, preemptive efforts, reformative and rehabilitative efforts. Reformative and rehabilitative efforts include prevention and handling efforts. Prevention is carried out through socialization of the dangers of drugs, strengthening the role of families, and integrating anti-drug curriculum in schools. Handling involves medical rehabilitation, psychosocial therapy, and social support for perpetrators of drug abuse, as well as strict action against dealers. The obstacles faced by the police in overcoming the circulation of methamphetamine among students today are: lack of education about the dangers of drugs in schools, limited access to rehabilitation services, drug abuse by figures idolized by students, and peer pressure to try drugs. The ideal formulation of police efforts in combating the circulation of crystal methamphetamine among students in the future is with a holistic approach, involving prevention, strict law enforcement, rehabilitation, and community empowerment. Prevention efforts must focus on education, socialization of the dangers of drugs, and strengthening the role of families and schools.